THE IMPACT OF ANXIETY ON ENGLISH SPEAKING TEST PERFORMANCE: A STUDY OF STUDENTS EXPERIENCES IN ISLAMIC HIGHER EDUCATION - Hasibuan, Sri Wahyuni (Journal of English Education and Linguistics, 2025)
This study aims to determine what types of anxiety students face in speaking test performance and how anxiety impacts students' speaking test performance. The research methodology is descriptive qualitative method. The research subjects were 15 students of English Education department in the third semester with Advanced Listening subject. The data were collected by doing interview, observation and documentation. Interview were done to collect data about types of anixety, and the observation were done to collect data about the impact of students anxiety on speaking test performance. The findings were there were 3 types of anxiety found in this study, namely cognitive, somatic and behavioral anxiety. Cognitive anxiety is experienced by 11 students, somatic anxiety is experienced by 10 students and behavioral anxiety is experienced by 7 students. The impact of anxiety on speaking class performance namely reduced fluency and coherence, limited use of vocabulary and grammar, limited use of vocabulary and grammar.